Implementation of Guided Inquiry to Increase Students’ Interest in Learning Physics and Critical Thinking Skills - Putri, Jayanti Kharisma; Gunawan, Cahya Widya; Wiyatmo, Yusman (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
The guided inquiry learning model is a pedagogical approach that has demonstrated significant potential to enhance students' critical thinking abilities and their interest in learning. This study aims to examine the extent of improvement in students' critical thinking skills and learning interest through the application of practicum media integrated with the guided inquiry learning model. The research methodology employed in this study follows the Research and Development (R&D) framework, utilizing the 4D model (Define, Design, Develop, Disseminate) to systematically design and evaluate the instructional approach. The research was conducted over a period of two months at SMA Negeri 1 Sewon, involving 35 students from class X-9 as the sample. The students participated in guided inquiry-based learning activities that incorporated practicum media specifically designed for this study. To evaluate the outcomes, a descriptive statistical analysis was conducted using normalized gain scores to measure the improvement in students' critical thinking skills and interest in learning. The results of the study indicate a significant increase in both students' critical thinking abilities and their engagement with the learning material after the implementation of the guided inquiry learning model with practicum media. These findings suggest that the guided inquiry model not only facilitates the development of critical cognitive skills but also enhances student motivation and involvement in the learning process. Given these results, it is evident that the guided inquiry learning model, when supplemented with practicum media, provides a promising instructional strategy for improving both cognitive and affective domains of learning. Further research is recommended to explore the applicability of this model in different educational contexts and across various disciplines to confirm the generalizability of these findings.